Civil Society, Conflict and Violence - List, Regina A. (CIVICUS Global Study of Civil Society Series, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book looks at the role that civil society organizations play in dealing with conflict and violence. The authors argue that in most of the prevalent conceptualizations the conflict dimension of civil society is either downplayed or inadequately addressed. They contend that the ability to deal with conflict is at the heart of organized civil society; in the political process, one of civil society's key functions is to express and mediate between different interests, thus contributing to political decision-making. The chapters draw on detailed, empirical data from the CIVICUS Civil Society Index - a unique comparative data-set drawn from 25 countries, which has not previously been made publicly available. It examines the different ways violence has been manifested in civil societies, the meaning of violent protest and the impact of security legislation that might hinder the mediating efforts of civil society. The book offers a sophisticated comparison between conflict and post-conflict countries and an analysis of the role of civil society in conflict resolution, reconciliation and transitional justice.